Liver cirrhosis in HIV/HCV ‐coinfected individuals is related to NK cell dysfunction and exhaustion, but not to an impaired NK cell modulation by CD 4 + T‐cells - Polo, María L. (2019)
Introduction HIV worsens HCV‐related liver disease by accelerating fibrosis progression; however, progression rates are extremely variable among HIV/HCV‐coinfected individuals. NK cells are associated with modulation of liver fibrosis and are profoundly altered during HCV and HIV infections. CD4+ T‐cells modulate NK cell function, and are also affected by HIV infection. Here, we aim to characterize the association of hepatic fibrosis with both the phenotype and function of peripheral NK cells and their regulation by CD4+ T‐cells, in HIV/HCV‐coinfected individuals. Methods Thirty‐four HIV/HCV‐coinfected individuals with minimal (n = 16) and advanced (n = 18) fibrosis (METAVIR F0/F1 and F4 scores respectively) and 20 healthy volunteers were enrolled. PBMC were obtained from peripheral blood samples and NK and CD4+ T‐cells were isolated and analysed. NK cell phenotype (CD25, CD69, Nkp46, NKG2D, PD‐1), degranulation (CD107a) and IFN‐γ and TNF‐α production, as well as CD4+ T‐cell activation (CD69, CD25 and CD38) were measured by flow cytometry. CD4+ T‐cell conditioned medium (CM) derived from F0/F1 or F4 individuals was assessed for IL‐2 levels by ELISA. Modulation of NK cell functionality by these CMs was also analysed. Results When comparing to NK cells from individuals with minimal fibrosis, degranulation and cytokine secretion by NK cells from subjects with F4 scores was significantly impaired, while PD‐1 expression was augmented. On the one hand, neither the expression of activation markers nor IL‐2 secretion was distinctly induced in CD4+ T‐cells from subjects with F0/F1 or F4 METAVIR scores. Finally, NK cell degranulation and cytokine secretion were not differentially modulated by CD4+ T‐cell CM, whether CD4+ T‐cells derived from subjects with minimal or advanced fibrosis. Conclusions Low levels of NK and CD4+ T‐cells in HIV/HCV‐coinfected individuals with advanced liver fibrosis have been previously described. Here, we show that advanced liver fibrosis in coinfected individuals is associated to a defective function of NK cells and an increased expression of the exhaustion/senescence marker PD‐1. This NK signature could not be attributed to changes in the ability of CD4+ T‐cells to modulate NK cell function.